Expanding Our Knowledge of Interstellar Neutral Hydrogen Shells - Laszczkowski, Tyler; Sallmen, Shauna (Proceedings of the Wisconsin Space Conference, 2015)
The purpose of this research is to increase the number of Galactic neutral hydrogen (HI) shells available for study. By identifying and studying more HI shells at various stages of their evolution, we can start to fill the gap in our understanding of the interactions of structures in the interstellar medium. This project consisted of visually identifying new HI Shells using 21-cm data downloaded from the GALFA-HI online database. This survey has higher angular resolution than the data used in previous searches, allowing us to discover smaller features. The results include a new list of previously undiscovered shell-like HI features along with measurements of their basic properties: location, mean angular diameter, shape, signs of expansion. Upon completing the search of 1/7th of the data cubes containing complete GALFA data, 141 potential shells were discovered. Additionally, one pattern appeared several times while identifying potential shells. This pattern can be described as a â€œfigure-eightâ€ feature composed of two features that are likely related. The completion of this project has expanded the current database of potential HI Shells in our galaxy, which can be used to provide important data in regards to the study of shell evolution and the role of shells within the ISM.